Religious Tolerance Model of Society in Jepara: Principles Analysis of Freedom, Acceptance, and Trust - Setiadi, Ozi; Qodarsasi, Umi; Khoiruzzaman, Wahyu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Religious tolerance supports the conduciveness of society. This has far more impact on a religious country like Indonesia than it does on a secular one. In a religious country, religion has two sides, namely functional and dysfunctional. The functional side of religion can create peace. Conversely, the dysfunctional side of religion can lead to conflict in society. This study aims to analyze the model of religious tolerance that has developed in Jepara society. This research is a field research with a qualitative approach. Data collection techniques were carried out using semi-structured interviews with purposive sampling. Data were analyzed using Miles and Huberman's data analysis framework. The results of this study show that the Jepara people have a strong tolerance value. The religious tolerance of the Jepara people turns out to have three main principles, namely the principle of religious freedom, the principle of acceptance, and the principle of positive thinking and trustworthiness. These principles then become a separate model in the implementation of religious tolerance in Jepara society. This model of tolerance is able to support religious conduciveness which then has an impact on the conduciveness of various aspects, such as social aspects.